2006
DOI: 10.1063/1.2360219
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet photodetectors with ZnO nanowires prepared on ZnO:Ga/glass templates

Abstract: Vertically well-aligned ZnO nanowire ultraviolet ͑UV͒ photodetectors were fabricated by spin-on-glass technology on ZnO:Ga/glass templates. With 2 V applied bias, it was found that dark current density of the fabricated device was only 2.0ϫ 10 −7 A/cm 2 . It was also found that UV-to-visible rejection ratio and quantum efficiency of the fabricated ZnO nanowire photodetectors were more than 1000 and 12.6%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 28 publications
(5 reference statements)
0
54
0
1
Order By: Relevance
“…32 Experimentally was reported that the (002) crystallographic plane is strongly dependent upon the O 2 gas in sputtered ZnO lms. 33,34 The formation and ZnO growth is promoted when increasing the [NH 4 OH] in the solution allowing more atomic oxygen in the ZnO unit cell until a pH value about 10.94. The XRD results conrms the SDDS predictions, otherwise these results may indicate a change in the morphology of the ZnO lms surface.…”
Section: Resultsmentioning
confidence: 99%
“…32 Experimentally was reported that the (002) crystallographic plane is strongly dependent upon the O 2 gas in sputtered ZnO lms. 33,34 The formation and ZnO growth is promoted when increasing the [NH 4 OH] in the solution allowing more atomic oxygen in the ZnO unit cell until a pH value about 10.94. The XRD results conrms the SDDS predictions, otherwise these results may indicate a change in the morphology of the ZnO lms surface.…”
Section: Resultsmentioning
confidence: 99%
“…Smooth and uniform growth of ZnO nanowire array with high aspect ratio is synthesized by low temperature hydrothermal method. Their amazing performance in photonics, optics and electronics ZnO NWs become much appealing candidates for multiple uses such as light-emitting diodes [14], gas sensors [15], UV lasers [16], solar cells [17], photo-detectors [18], resistive switching [19] and photo-catalysts [20].…”
Section: Mansoor Hussainmentioning
confidence: 99%
“…As an alternative, many researchers are trying to explore the low-cost, environment friendly and wide band gap (~3.34 eV) zinc oxide (ZnO) material with large exciton energy (~60 meV larger than GaN ~25 meV) for the UV detection applications [5,6]. They have shown their interest to investigate ZnO based UV photodetectors with different configurations such as Schottky diode [5,6], MSM (metal-semiconductor-metal) [3,7,8], MISM (metalinsulator-semiconductor-metal) [2,8] and p-n heterojunction [9][10][11][12][13] photodiode structures. Since, ZnO is an intrinsically n-type semiconductor, the fabrication of a stable and controllable p-type ZnO thin film is very difficult [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among various substrates used for the ZnO thin film based UV detectors [5][6][7], Si can be considered to be of special interests because of its compatibility with the modern days CMOS technology [11]. The ZnO thin films can be deposited on large Si wafer by various chemical and physical methods such as vapour transport [9], hydrothermal [10], thermal evaporation [11], pulsed laser deposition (PLD) [14], magnetron sputtering [15], atomic layer deposition (ALD) [16,17] and sol-gel techniques [12,13].…”
Section: Introductionmentioning
confidence: 99%